Motivation, COVID-19 Stigma, Knowledge, and Perception About the Vaccine Among the Public Who Have Received the COVID-19 Vaccine: Motivasi, Stigma Covid, Pengetahuan Dan Persepsi Tentang Vaksin Pada Masyarakat Yang Melakukan Vaksin Covid 19 - Lukas Diono (Indonesian Journal of Administration and Health Research (IJAHR), 2024)
This study aims to examine the motivation, COVID-19 stigma, knowledge, and perceptions about vaccination among the community in the Suka Bangun Health Center area. This descriptive research with a cross-sectional design involved 387 respondents from a population of 11,518 individuals who had not been vaccinated by December 31, 2021. The sample was selected using proportional sampling and data were collected through interviews using Kobo Collect. Data analysis was conducted univariately to observe proportions and tendencies. The results showed that 91.7% of respondents were motivated to vaccinate for administrative purposes, 83.1% out of fear of contracting COVID-19, and 70.5% were encouraged by family members. Additionally, 80.4% had a COVID-19 stigma, 67.7% had good knowledge about vaccines, and 73% had a positive perception of vaccination. These findings highlight the need for intensive socialization on the benefits of vaccination, involving religious and community leaders to change perceptions about vaccines, and future health education interventions to increase knowledge about COVID-19 through mass media. Health workers play a crucial role in promoting vaccination, countering misinformation, and providing support and protection for individuals with COVID-19 in the community.Penelitian ini bertujuan untuk mengetahui motivasi, stigma COVID-19, pengetahuan, dan persepsi masyarakat tentang vaksinasi di wilayah Puskesmas Suka Bangun. Penelitian deskriptif dengan desain cross-sectional ini melibatkan 387 responden dari populasi 11.518 yang belum divaksin hingga 31 Desember 2021. Sampel diambil dengan teknik proportional sampling melalui wawancara menggunakan Kobo Collect. Analisis dilakukan secara univariat untuk melihat proporsi dan kecenderungan. Hasil menunjukkan bahwa 91,7% responden divaksin untuk memudahkan administrasi, 83,1% karena takut tertular, dan 70,5% disarankan oleh orang tua/kerabat. Sebanyak 80,4% memiliki stigma COVID-19, 67,7% memiliki pengetahuan baik tentang vaksin, dan 73% memiliki persepsi positif terhadap vaksinasi. Hasil ini menunjukkan pentingnya sosialisasi tentang manfaat vaksinasi kepada masyarakat, melibatkan tokoh agama dan masyarakat dalam mengubah persepsi terkait vaksin, serta intervensi pendidikan kesehatan untuk meningkatkan pengetahuan tentang COVID-19 melalui media massa. Peran petugas kesehatan sangat penting dalam mempromosikan vaksin, menangkal hoaks, dan memberikan dukungan serta perlindungan bagi penderita COVID-19.